Enhancing EFL Saudi university students' speaking proficiency through TED talks - Khaled A. Alghmadi (Journal of Pedagogical Research, 2024)
The study aims to determine whether exposing EFL Saudi undergraduate students to TED talks could effectively contribute to the improvement of their oral language proficiency. To achieve this goal, 32 English as a Foreign Language Saudi undergraduate students were recruited to participate in the study. These students were selected based on their willingness to engage in the study and their availability for participation. The study employed a pre-test and post-test design, indicating that the participants' oral skills were assessed both before and after they were exposed to the TED talks. This design enables the researchers to measure the potential improvement in oral skills by comparing the scores obtained from the two tests. The test scores were evaluated across multiple dimensions, including fluency, content, vocabulary, grammar, and pronunciation. The results indicated that the overall scores of the EFL students improved after they watched the TED talks. This improvement suggests that the exposure to TED talks had a positive impact on the participants' oral skills, particularly in terms of fluency, which was the primary focus of the study.